Bowel-associated dermatosis-arthritis syndrome (BADAS): a narrative review - Czajkowski, Rafał; Lipska, Patrycja; Watoła, Wiktoria; Grabowska, Nicole; Wełniak, Adam (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
Bowel-associated dermatosis-arthritis syndrome is a neutrophilic dermatosis presenting with flu-like symptoms, arthritis and skin lesions. The type of skin presentation varies although typically consists of red patches progressing into papulopustular-type lesions. Initially, the pathogenesis of the disease was linked exclusively to bariatric surgery, but more recent reports indicate the role of gastrointestinal diseases resulting in bacterial overgrowth and consequent translocation of bacteria into the bloodstream. The disease may resolve spontaneously, however sometimes requires a treatment aimed at managing inflammation and excessive bacterial overgrowth, and therefore antibiotic therapy, immunosuppressive drugs, biological treatment and sometimes intestinal surgeries are applied.